Currículos alternativos/oficiais: o(s) risco(s) do hibridismo - Sandra Corazza Mara (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
The article stresses the discursive similarities between the National Curricula Parameters (PCN) established by the Brazilian Ministryof Education, considered the official curriculum, and the School Assembly Movement inspired by the Workers´Party state government in Rio Grandedo Sul, proposed as an alternative curriculum. It discusses what has been happening with our critical alternative curricula which end upproposing almost the same educationas that of the Federal Government. It forwards the argument that, as aconsequence of this hybridism, weneed to dispel the ambiguity, by producing and putting into practice curricula which do not yet exist and to invent once more the difference.